2019
DOI: 10.1101/514836
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A neuroprosthetic system to restore neuronal communication in modular networks

Abstract: 48Recent advances in neurotechnology allow neurological impairments to be treated or 49 reduced by brain machine interfaces and neuroprostheses. To develop energy-efficient and 50 3 real-time capable devices, neuromorphic computing systems are envisaged as the core of 51 next-generation 'neurobiohybrid' systems for brain repair. We demonstrate here the first 52 exploitation of a neuromorphic prosthesis to restore bidirectional interactions between two 53 neuronal populations, even when one is damaged or com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…Another point is to increase the degree of precision by designing multi-compartmental neurons and give a real-time tool to neuroscientist to simulate their neuron structure with different parameters. To conclude, this biomimetic SNN platform can provide better solutions for biomedical application especially in neuroprosthesis (Buccelli et al, 2019) and therapeutics protocol for neurological diseases.…”
Section: Discussionmentioning
confidence: 95%
“…Another point is to increase the degree of precision by designing multi-compartmental neurons and give a real-time tool to neuroscientist to simulate their neuron structure with different parameters. To conclude, this biomimetic SNN platform can provide better solutions for biomedical application especially in neuroprosthesis (Buccelli et al, 2019) and therapeutics protocol for neurological diseases.…”
Section: Discussionmentioning
confidence: 95%
“…We previously showed that our system can be connected to biological neurons [22,23]. Another advantage is that the real-time systems can simulate multiple CPG topologies and simulate different hypothesis and protocol treatments for biomedical applications such as spinal cord injury [24] and neuroprosthetics [25,26].…”
Section: Resultsmentioning
confidence: 99%
“…These signals express important biomarkers symptomatic of various neurodegenerative diseases, e.g., Parkinson disease (Lehmkuhle et al, 2009), and provide great opportunities for clinical applications. Moreover, especially in the interaction with biological central pattern generators, biohybrid systems profit from this type of recording, as illustrated by Buccelli et al (2019), where the authors use bursts to trigger spiking activity in the ANN side of their biohybrid. In situations where either spatial or temporal resolution prohibits the focus on single unit activity, signals undergo extensive signal conditioning before feature extraction.…”
Section: Information Processing At the Ann/bnn Interfacementioning
confidence: 99%
“…The most straightforward approach here is the triggering of single stimulus waveforms whenever an event occurs in the output population of the ANN. This, however, requires the experimental selection of parameters in the stimulation waveform (Buccelli et al, 2019;Jung et al, 2001). With the argument that high stimulation frequencies have adverse fatigue effects Eftekhar et al, 2007 focus on a modulation of the stimulation current amplitude, rather than a direct translation of spike to stimulus.…”
Section: Ll Open Accessmentioning
confidence: 99%
See 1 more Smart Citation